Rearrangement Reactions of Tritylcarbenes: Surprising Ring Expansion and Computational Investigation1. Issue 42 (21st August 2015) - Banert, Klaus; Hagedorn, Manfred; Pester, Tom; Siebert, Nicole; Staude, Cornelius; Tchernook, Ivan; Rathmann, Katharina; Hollóczki, Oldamur; Friedrich, Joachim
Abstract As a rule, acetylides and sulfonyl azides do not undergo electrophilic azide transfer because 1, 2, 3‐triazoles are usually formed. We show now that treatment of tritylethyne with butyllithium followed by exposure to 2, 4, 6‐triisopropylbenzenesulfonyl azide leads to products that are easily explained through the generation of short‐lived tritylethynyl azide and its secondary product cyanotritylcarbene. Furthermore, it is demonstrated that tritylcarbenes generally do not produce triphenylethenes exclusively, as was stated in the literature. Instead, these carbenes always yielded also (diphenylmethylidene)cycloheptatrienes (heptafulvenes) as side products. This result is supported by static DFT, coupled cluster, and ab initio molecular dynamics calculations. From these investigations, the fused bicyclobutane intermediate was found to be essential for heptafulvene formation. Although the bicyclobutane is also capable of rearranging to the triphenylethene product, only the heptafulvene pathway is reasonable from the energetics. The ethene is formed straight from cyanotritylcarbene.